La réécriture des modèles français et américains dans Cadavres de François Barcelo - Sawicka, Sylwia (Romanica Silesiana)
The article presents François Barcelo’s roman noir “Cadavres” as an attempt at deconstructing the conventions of the literary genre. The definition of a “roman noir” is twofold. On one hand it is a gritty novel narrated by the perpetrator, on the other it delineates the dark side of the society. Barcelo’s novel transgresses the traditional model of the genre by the implementation of metafiction and elements of grotesque. Barcelo creates an original Quebecois crime novel by combining these two characteristics. In order to show the maladjustment and alienation of a social group, he creates an inept villain and transforms the setting of the novel, grotesquely turning an edgy metropolis into a boring provincial town. Thus “Cadavres” goes far beyond the existing French and American models of the black novel. Key words: François Barcelo; roman noir; metafiction; break with conventions